G.H. Kocks (Samesteller), J.P. Vording, A. Beugels, H. Bloemhof, e.a. (Medewerkers). Woordenboek van de Drentse Dialecten, A-L. - van der Merwe, G.S. (Lexikos, 1997)
Review of G.H. Kocks (Samesteller), J.P. Vording, A. Beugels, H. Bloemhof, e.a. (Medewerkers). Woordenboek van de Drentse Dialecten, A-L.